Медиалингвистика как когнитивно-коммуникативный дешифратор информационно-психологической войны - Шилина, А.Г. (Культура народов Причерноморья, 2014)
Статья посвящена описанию характера взаимоотношений системы языка и
медиасистемы в конце XX – начале XXI ст. Результатом подобного контакта стали информационные
войны, представляющие собой одну из сфер функционирования современного русского литературного
языка. Научно-методологическим «ключом» в дешифровании информационной, информационно-
психологической, войны выступила медиалингвистика. Ее базовые категории медиасверхтекст,
медиатекст и медиажанр трансформировались в таковые и в информационно-психологической войне,
которая с учетом медиалингвистических подходов идентифицируется как когнитивно-
коммуникативная система-сверхтекст. Стаття присвячена описові характеру взаємозв’язку системи мови та медіасистеми кінця
XX – початку XXI ст. Результатом такого контакту стали інформаційні війни, які є однією зі сфер
функціонування сучасної російської літературної мови. Науково-методологічним «ключем» у
дешифруванні інформаційної, інформаційно-психологічної, війни виступає медіалінгвістика. Її базові
характеристики медіасупертекст, медіатекст і медіажанр трансформувалися в подібні й в
інформаційно-психологічній війні, що з урахуванням медіалінгвістичного підходу ідентифікується як
когнітивно-комунікативна система-супертекст. This article is devoted to the description of mutual relations of the language system and media
system, which acquired bilateral nature in the end of XX – the beginning of XXIcenturies. On the one hand
language processes were reflected in media discourse which transformed in some kind of experimental platform
for the language, and on the other hand modern mass media made some demands to the language. As the result
of such “experiments” and “prescriptions” we see informational wars which present one of the spheres of
modern literary Russian language functioning. Medialinguistics became the science and methodological “key”
for the decryption of informational or informational and psychological warfare. Its base categories such as
mediasupertext, mediatext and mediagenre were transformed in the same in the informational and psychological
warfare. By the help of medialinguistical approaches this war was identified as cognitive and communicative
supertextsystem which has strict localand chronological borders; topical and modal wholeness; simultaneous
openness and closeness of borders; it is the formation of authors team; the ability of homeostasis (the kind of
text structure); non-linearity that is displayed in dialogism, carnivalization, language game, experimental forms,
mosaic of the picture of the world, performance and cross-genre.